Pengaruh Kualitas Layanan dan Harga Terhadap Loyalitas Pelanggan Pada Jasa Pengiriman JNE Di Surabaya Selatan - Rispa Rispa; Iswati Iswati; Anis Fitriyasari (Jurnal Manajemen dan Ekonomi Kreatif, 2024)
This research aims to find out more about "The influence of service quality and price on customer loyalty for JNE delivery services in South Surabaya". In accordance with the main issue that raises the influence of service quality and price on customer loyalty at JNE in South Surabaya, the background for this research is that in the midst of intense competition among delivery service companies and the increasing increase in online purchases, of course every delivery service provider must focus on providing the best service and The prices offered are relatively cheap according to the target market to strengthen customer loyalty. The aim of this research is to find out the effect of service quality on customer loyalty at JNE delivery services in South Surabaya, to find out the effect of price on customer loyalty at JNE delivery services in South Surabaya, and to find out the effect of service quality and price on customer loyalty. on JNE delivery services in South Surabaya. The method used in this research is quantitative which aims to find out how big the influence is between the variables to be studied. To support this research, expand the distribution of questionnaires using a Likert scale. The sample in this research used the Purposive Sampling Technique, which is a technique for determining samples using certain considerations and criteria. The population in this study were JNE delivery service users in South Surabaya. The number of samples in this research was 60 respondents. After distributing the questionnaire, the results were calculated using SPSS. The conclusion of this research is that Service Quality has no influence on JNE customer loyalty in South Surabaya, Price has a significant influence on JNE Customer Loyalty in South Surabaya, Service Quality and Price simultaneously influence JNE Customer Loyalty in South Surabaya.